2022
DOI: 10.5371/hp.2022.34.3.140
|View full text |Cite
|
Sign up to set email alerts
|

Periprosthetic Fracture around a Cemented Stem in Total Hip Arthroplasty

Abstract: The increase in the number of primary total hip arthroplasties that will be performed over the next several decades will lead to an increase in the incidence of periprosthetic fractures around the femoral stem. A search of targeted articles was conducted using on-line databases of PubMed (National Library of Medicine) and articles were obtained from January 2008 to November 2021. Reliable prediction of treatment can be achieved using the Vancouver classification; internal fixation is indicated in fractures inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…By using data from the NJR, they identified 2,158 primary THA employing this implant and found a revision risk that was nearly double that observed with the standard Exeter ® stem at 10-years follow-up [ 10 ]. Periprosthetic fracture was one of the largest contributors to the revision of the SRS stem [ 10 ], which is consistent with the increased risk associated with the collarless polished taper slip design [ 24 , 25 ]. A systematic review by Thompson et al [ 24 ] found 25 reported cases of prosthetic fractures of Exeter ® stems and demonstrated that short (125 mm) stem length was more likely to fracture, and of the seven reported short stems, four were SRS (44/00/125).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…By using data from the NJR, they identified 2,158 primary THA employing this implant and found a revision risk that was nearly double that observed with the standard Exeter ® stem at 10-years follow-up [ 10 ]. Periprosthetic fracture was one of the largest contributors to the revision of the SRS stem [ 10 ], which is consistent with the increased risk associated with the collarless polished taper slip design [ 24 , 25 ]. A systematic review by Thompson et al [ 24 ] found 25 reported cases of prosthetic fractures of Exeter ® stems and demonstrated that short (125 mm) stem length was more likely to fracture, and of the seven reported short stems, four were SRS (44/00/125).…”
Section: Discussionmentioning
confidence: 70%
“…However, there were no reported SRS fractures in the current series and the survival was equal to that observed with a standard stem. There is also an associated increased risk of periprosthetic fracture with shorter stem length around a cemented polished taper stem implant, such as the Exeter ® stem [ 25 , 26 ]. Therefore the short-cemented Exeter ® stem may be subject to periprosthetic fracture, but the rate in the current series was low.…”
Section: Discussionmentioning
confidence: 99%
“…However, no data are available in the literature on the dislocation rate in THR for PFF with a monoblock stem. Further studies will be needed to better estimate the dislocation rate in this patient cohort ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of an aging population has resulted in a notable increase in THA surgeries, which in turn has led to a rise in postoperative PFFs. Research indicates that individuals who are 85 years of age or older are especially susceptible to adverse effects following a hip fracture, including diminished functional outcomes and elevated mortality rates [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…An additional crucial factor to consider is the influence of sarcopenia and osteoporosis on the elderly population, rendering them more prone to falls and less capable of withstanding impact. Consequently, this elevates the likelihood of experiencing proximal femoral fractures [7,14]. This article aims to examine the present understanding of PFFs, taking into account their growing prevalence, the developing classification systems, the influence of implant selection, and the significance of patient-specific risk factors.…”
Section: Introductionmentioning
confidence: 99%